2006
DOI: 10.1007/s00439-006-0251-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetically balanced translocations are associated with focal copy number alterations

Abstract: Current cytogenetic methods (e.g., G-banding and multicolor chromosomal painting) allow detection of translocation events but lack the resolution to (a) locate the breakpoints precisely at the chromosome band level or (b) discriminate balanced translocations from translocations with copy number alterations not previously reported, or imperfectly balanced translocations. In this study, we demonstrate that cytogenetically balanced translocations are in fact frequently associated with segmental gain or loss of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
(40 reference statements)
1
35
0
1
Order By: Relevance
“…A recurrent chromosomal breakpoint (Mitelman, 1984(Mitelman, , 1986 is immediately adjacent to the PRCC and NTKR1 genes (Mitelman et al, 2009), although this breakpoint has been associated mainly with hematopoietic tumors. As further evidence of the need to exclude such a mechanism in our study, translocation events have been identified as a source of copy number change (Watson et al, 2007).…”
Section: Discussionmentioning
confidence: 52%
“…A recurrent chromosomal breakpoint (Mitelman, 1984(Mitelman, , 1986 is immediately adjacent to the PRCC and NTKR1 genes (Mitelman et al, 2009), although this breakpoint has been associated mainly with hematopoietic tumors. As further evidence of the need to exclude such a mechanism in our study, translocation events have been identified as a source of copy number change (Watson et al, 2007).…”
Section: Discussionmentioning
confidence: 52%
“…DNA was isolated by proteinase K digestion followed by phenol-chloroform extraction. Array hybridization was performed as previously described (Lockwood et al, 2007), using SMRT array v.2 Watson et al, 2007). Array images were analysed using SoftWoRx Tracker Spot Analysis software (Applied Precision, Issaquah, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Even balanced translocations are often identifiable based on subtle hybridization variation at the breakpoints in DNA (or in fusion transcripts). [103][104][105] Identification of microdeletions or duplications, as well as cryptic translocations, may add value when interpreted in combination with results of traditional metaphase cytogenetics. 106 Full-genome sequencing is now feasible and may reveal novel factors responsible for tumor initiation and progression.…”
Section: Microarray-based Gene Copy Number Variants and Whole-genome mentioning
confidence: 99%